Deep Back Massage as Therapy For Labor Pain In The 1st Stage - Sri Rejeki; Tri Wahyu Novianti; Machmudah Machmudah; Nikmatul Khayati (Universitas Muhammadiyah Semarang, 2022)
Pain is always felt by the mother in the labor process. Pain is a physiological process of the body caused by uterine contractions. The pain felt by the mother ranged from mild to severe pain. Severe pain can result in neurogenic shock, so the labor process takes a long time. Therefore, this pain needs to be treated. Non-pharmacological pain therapy is an alternative to reduce labor pain. The purpose of this study was to determine the effect of back massage (deep back massage) on the intensity of labor pain in the first stage. This study uses the Quasy Experiment with one group pretest-posttest design. The sampling technique used purposive sampling and obtained 35 intrapartum mothers with the inclusion criteria: Mothers with term pregnancy (37-41 weeks), vaginal delivery in the first stage of the active phase, up to 10 cm, single fetus and mother can communicate verbally. Before doing back massage therapy, the mother was given a sheet. The study was carried out according to the procedure, namely giving a massage on the back for 20 minutes then the intensity of pain was measured by NRS (Numeric rating scale) post-test with a distance of 5-10 minutes after being given a back massage. The data after the Shapiro-Wilk normality test and Wilcoxon test data analysis showed that before the back massage the mean was 6.23, while after the back massage the mean was 5.14. The results of the analysis show p-value = 0.000 (0.000). Conclusion: There is an effect of back massage on the intensity of maternal pain in the first stage of labor